Problematika yang dihadapi anak alur di Desa Sei Sembilang Kabupaten Asahan - Nasution, Diana Lestari; Andriansyah, Dedi (Jurnal Sosial Ekonomi Perikanan, 2023)
The research was carried out with the aim of describing the problems faced by Anak Alur in Sei Sembilang Village, Asahan district. The research method used ethnographic methods with data collection techniques through participation observation, in-depth interviews with documentery informants, and using field notes. The results of the study explained that in dealing with the navigating in the buttocks and in the forest, the research results have found several problems faced by childern, namely regarding safety and health. When fishing Alur’s childern will face various kinds of problems when fishing.